The Rhetorical Functions of Scriptural Quotations in Romans, Paul's Argumentation by Quotations. - Katja Kujanpää (Novum Testamentum, Supplements, 2019)
Quotations from Jewish scriptures play a crucial role in the Letter to the Romans. The Rhetorical Functions of Scriptural Quotations in Romans explores their rhetorical functions in Paul's argumentation. It offers a careful text-critical analysis of the 51 quotations in Romans, and asks questions such as: does Paul quote accurately according to a wording known to him or does he adapt it himself? Moreover, to what extent does Paul strive to preserve the sense that the quoted words have in their original context? Katja Kujanpää's approach of combining rhetorical matters with close textual study results in a more comprehensive picture of quotations in Romans than has been previously seen. Thus, the book opens new perspectives on Paul's argumentation, rhetoric and theological agenda.